Fatigue performance evaluation for ITER IVC conductor component materials. (November 2017) - Jin, H.; Vostner, A.; Wu, Y.; Macioce, D.; Sgobba, S.; Huang, C.; Romero Rodriguez, C.; Fernandez Pison, P.; Elisabeth Langeslag, S.A.; Aviles Santillana, I.; Long, F.; Yu, M.; et al.
Abstract: The ITER IVCs are made of stainless steel mineral-insulated conductors composed by an OFE copper conductor and a SS316LN jacket. The baseline design requires the coils to endure all ITER machine life time. After a brief review of past and recent literatures, no results are available and of our interest. Moreover, cold working, aging treatments as well as the environment temperature affect the mechanical and fatigue properties. The present paper summarizes data from tensile and uniaxial tension load controlled fatigue tests on both the steel jacket and the copper conductor in the IVC representative operation conditions. Tests are performed on specimens sectioned from the tubes undergone cold working of conductor compaction, coil winding and so on as well as heat treatment at 240 °C for 24 h of baking, and finally tested at operation temperature of 120 °C. The fatigue tests were conducted at frequency of 15 Hz and the stress ratio of R = 0.1. Results from tensile tests show both strength and ductility decrease as temperature rises from RT to 120 °C. Results from fatigue tests are presented as S-N relationships with the maximum stress expressed as a percentage of the strength under static loading. It was found that the fatigue strength limit for OFE copper conductor and SS316LN jacket were close to 120 MPa and 275 MPa respectively. The influence from residual stresses on the static and fatigue performance of 316LN jacket were also investigated It was found that the ductility and fatigue life can be improved by residual stress releasing of heat treatment at 650 °C for 100 h. Highlights: OFE copper and SS316LN tubes were undergone compaction, stretching and 240 °C baking for 24 h. Typical S-N curves for OFE copper and SS316LN tubes were determined. Residual stress affects the tensile and fatigue strength of SS316LN. Heat treatment at 650 °C for 100 h can release part of the residual stress for SS316LN tube. Residual stress relief can improve the elongation and fatigue strength.